2005
DOI: 10.1002/anie.200462857
|View full text |Cite
|
Sign up to set email alerts
|

A Microfluidic Approach for Screening Submicroliter Volumes against Multiple Reagents by Using Preformed Arrays of Nanoliter Plugs in a Three‐Phase Liquid/Liquid/Gas Flow

Abstract: Plugging a gap in screening-Arrays of nanoliter-sized plugs of different compositions can be preformed in a three-phase liquid/liquid/gas flow. The arrays can be transported into a microfluidic channel to test against a target (see schematic representation), as demonstrated in protein crystallization and an enzymatic assay.Keywords crystal growth; enzymatic arrays; microreactors; screening methods; three-phase system Herein, we describe a simple, economical microfluidic method of screening a small volume (down… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
201
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 217 publications
(204 citation statements)
references
References 31 publications
(34 reference statements)
1
201
1
1
Order By: Relevance
“…To perform simultaneous hybrid screening and optimization, we used plugs [droplets surrounded by fluorinated carrier fluid and transported through microfluidic channels (24)]. Plugs have been used to perform the initial screening in a number of applications, including biochemical assays (25), chemical reactions (26), and crystallization of soluble proteins (22). In separate experiments, plugs have been used for optimization of protein crystallization conditions (23).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To perform simultaneous hybrid screening and optimization, we used plugs [droplets surrounded by fluorinated carrier fluid and transported through microfluidic channels (24)]. Plugs have been used to perform the initial screening in a number of applications, including biochemical assays (25), chemical reactions (26), and crystallization of soluble proteins (22). In separate experiments, plugs have been used for optimization of protein crystallization conditions (23).…”
Section: Resultsmentioning
confidence: 99%
“…1): (i) To deliver many distinct reagents in the same experiment, as required for the initial screen, we used a preformed array of reagent plugs, each plug Ϸ120-140 nl in volume. Each pair of plugs in the array was separated by Ϸ40-nl spacer to ensure reliable transport of reagent plugs of different viscosities and surface tensions (22,27). As this array was flowed from the cartridge into the microfluidic device, each plug formed a long segment that could be manipulated as a continuous stream (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the generation of droplets with a predictable and reproducible size and size distribution determines their potential applications (including the synthesis of polymer colloids), several research groups have explored various aspects of the process of emulsification (Seo et al 2005a;Xu et al 2005;Zhang et al 2006;Cygan et al 2005;El-Ali et al 2005;Garstecki et al 2005a;Hudson et al 2005;Jensen and Lee 2004;Khan et al 2004;Song et al 2003;Zheng and Ismagilov 2005;Zheng et al 2003) . It has been observed that the size of droplets is controlled by the design of the microfluidic device (Sugiura et al 2002a, b;Tan et al 2006), the properties of liquids, and the rates of flow of two immiscible phases (Cramer et al 2004;GananCalvo 1998;Ganan-Calvo and Gordillo 2001;Garstecki et al 2004Garstecki et al , 2005aGarstecki et al , 2005bGarstecki et al , 2006Thorsen et al 2001;Serra et al 2007;Tice et al 2003;Ward et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The compartmentalization of reactions in droplets provides rapid mixing of reagents, flexible control of sample volumes, and prevention of water evaporation and cross contamination between samples [1][2][3]. These advantages of droplet-based microfluidics have shown benefits to a wide range of chemical and biological applications, such as enzymatic kinetics [4][5][6], protein crystallization [7][8][9], polymerase chain reaction [10][11][12] and clinical diagnosis [13].…”
Section: Introductionmentioning
confidence: 99%